Peningkatan Hasil Belajar Melalui Modifikasi Media Pembelajaran Siswa Kelas 2 Madrasa Aliyah Negeri Ambon - Asnawi, Siti; Syaranamual, Jusak; Tahapary, Johni Melvin (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2023)
This research is a class action research (PTK) that is carried out in two cycles and each cycle consists of 2 meetings with research subjects of 2nd grade students of 20 students. Data sources come from students, teachers, and researchers. Data collection techniques using tests and observations. Data validation using data triangulation techniques. Data analysis using qualitative descriptive analysis techniques using percentage techniques. In pre-cycle I the percentage of completion was 73.2%. Unfinished students were 10 and in cycle II 20 students were 79%. Based on the above analysis, it can be concluded that the use of learning modification tools can improve the learning outcome of back to back shooting in second grade students Man Ambon in the 2021/2022 academic year.